2016
DOI: 10.1186/s13048-016-0239-6
|View full text |Cite
|
Sign up to set email alerts
|

Strong synergy with APR-246 and DNA-damaging drugs in primary cancer cells from patients with TP53 mutant High-Grade Serous ovarian cancer

Abstract: BackgroundMutation in the tumor suppressor gene TP53 is an early event in the development of high-grade serous (HGS) ovarian cancer and is identified in more than 96 % of HGS cancer patients. APR-246 (PRIMA-1MET) is the first clinical-stage compound that reactivates mutant p53 protein by refolding it to wild type conformation, thus inducing apoptosis. APR-246 has been tested as monotherapy in a Phase I/IIa clinical study in hematological malignancies and prostate cancer with promising results, and a Phase Ib/I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 37 publications
1
46
0
3
Order By: Relevance
“…The combination index (C.I.) has been calculated by means of the following equation [41]: %PCV = % Predicted Cell Viability = % Cell Viability Drug1 x % Cell Viability Drug2 x 0.01. CI = Combination Index = % Measured Cell Viability Drug1 + Drug2 / %PCV.…”
Section: Discussionmentioning
confidence: 99%
“…The combination index (C.I.) has been calculated by means of the following equation [41]: %PCV = % Predicted Cell Viability = % Cell Viability Drug1 x % Cell Viability Drug2 x 0.01. CI = Combination Index = % Measured Cell Viability Drug1 + Drug2 / %PCV.…”
Section: Discussionmentioning
confidence: 99%
“…Since many chemotherapy drugs depend on wild-type p53 for induction of tumor cell apoptosis, the restoration of wild-type p53 by APR-246 has the potential to sensitize p53-mutant cancers to these drugs. Indeed, APR-246 has showed strong synergy with traditional chemotherapy drugs such as cisplatin, 5-fluorouracil and doxorubicin in multiple p53-mutant expressing ovarian cancers (52). Furthermore, mutant p53 targeting with APR-246 effectively eliminates resistance to the proteasome inhibitor carfilzomib (53).…”
Section: Compounds That Directly Target Mutant P53mentioning
confidence: 99%
“…Theoretically, at least half of all cancer patients would benefit from strategies targeting p53. Also, the combination of mutp53 reactivators and traditional anticancer drugs may exhibit synergetic effects, as conventional anticancer drugs usually depend on an intact p53 pathway (Deben et al, ; Fransson et al, ), which expands the application of mutp53 reactivators. Encouragingly, some of the mutp53 reactivators are in clinical trials; PRIMA‐1 Met (APR‐246) and COTI‐2 showed positive results (Deneberg et al, ).…”
Section: Discussionmentioning
confidence: 99%